AB1041 Office Extremity Magnetic Resonance Imaging (E-MRI) Can Differentiate Psoriatic and Rheumatoid Arthritis Without Contrast Enhancement. (9th June 2015) - Mathew, A.J.; Panwar, J.; Francis, I.; Koshy, V.; Danda, D.
Abstract : Background: Psoriatic arthritis (PsA), especially with symmetric polyarticular presentation, can often mimic rheumatoid arthritis (RA) clinically. Diagnosis of PsA can be challenging in patients without typical skin or nail lesions and in seronegative RA. Office e-MRI of small joints of hands could have a differential diagnosis value in addressing this issue. Objectives: The aim of this observational cohort study was to compare typical MRI findings of the hand in patients with PsA and RA. A secondary objective was to evaluate the reliability of two independent readers in scoring the OMERACT-RAMRIS and PsAMRIS-H variables, using a low field magnet office e-MRI machine, without contrast enhancement. Methods: Patients classified as PsA (CASPAR) and RA (2010 ACR/EULAR criteria), with symptomatic involvement of hand joints, attending a single tertiary care Rheumatology clinic between July 2013 and October 2014 were included and matched for age and disease duration. Demography, clinical and serological details were retrieved from electronic medical records. All patients underwent MRI of the dominant hand using standard protocols (3DT1-Cor, GESTIR-Cor, TSE-Tra, STIR-Tra, SE-Sag) in a 0.2T Esaote C-scan; Genova, Italy. Images were evaluated independently by two blinded readers in accordance with the OMERACT-RAMRIS and PsAMRIS-H scoring recommendations. Inter-observer reliability was calculated using correlation coefficient method. Univariate analysis of RAMRIS and PsARMRIS-H variables was done using parametric tests. Results: Eighteen patients were imaged in each group. Inter-rater reliability was excellent (ICC >0.9) for erosions and synovitis and very good (ICC >0.7) for tenosynovitis and bone marrow edema (BME). Diaphyseal bone marrow edema (DME), periosteal inflammation (PI) and flexor tenosynovitis (FT) at the first interphalangeal joint were exclusively present in PsA patients. Table 1 depicts the salient findings: Conclusions: Office e-MRI can distinguish PsA and RA without contrast enhancement, with PI, DME and FT as significant determinants. Excellent inter-rater reliability was noted in this study. This advanced imaging is patient friendly, economical as compared to the conventional MRIs, easily reproducible and can be used in outpatient clinics to aid in the differential diagnostic process in patients in whom diagnosis cannot be established unequivocally. References: Mathew AJ, Crues JV, Danda D. Office e-MRI: viewing joints from the inside. Int J Rheum Dis 2014;17:706-9. Ostergaard M, Edmonds J, McQueen F, et al. An introduction to the EULAR-OMERACT rheumatoid arthritis MRI reference image atlas. Ann Rheum Dis 2005;64(Suppl 1):3-7. Ostergaard M, McQueen F, Wiell Charlotte, et al. The OMERACT PsAMRIS: Definitions of key pathologies, suggested MRI sequences and preliminary scoring system for PsA hands. J Rheumatol 2009;36:1816-24 Disclosure of Interest: None declared